GENDER STEREOTYPES OF A WIFE CHARACTER IN A JAVANESE FILM MUDIK (2020) - Widodo, Jordy Satria; Priyatna, Aquarini; Mulyadi, Raden Muhammad (Journal Albion : Journal of English Literature, Language, and Culture, 2022)
Dadi Wong (Being a successful person) has been socialized through gender stereotypes in Javanese communities. The thought has also been contested with the opposite concept, namely Durung Tutug (Being an unsuccessful person). One can be included in either classification provided that he or she meets the criteria which are manifested in gender stereotypes. This article aims at identifying gender stereotypes of a Javanese wife character named Santi in film Mudik (2020). This article is analyzed using film narratology along with gender performativity and power relations. The elements, such as kernel and satellites, which show gender stereotypes of a Javanese wife character, Santi, were studied. The results present that Santi is represented as a wife who can not fulfill the criteria of Dadi Wong so that she is labelled Durung Tutug due to not having an intact family following her husbands passing. However, she negotiates it by getting married again with another man to meet the condition of Dadi Wong in Javanese society.  Keywords: film; gender stereotypes; Javanese wife; narratology.